ТЕРМИНЫ КАРАКАЛПАКСКОГО ЯЗЫКА И ИХ МЕТОДЫ ОБРАЗОВАНИЯ - Бердимуратова, А.Ж. (SCIENCE and SOCIETY, 2022)
A separate lexic of the Karakalpak language is always in the field of the view of researcher. Special lexic plays the most important role in science, where its use allows the most accurate transmission of scientific information of any degree of difficulty. Among the special verbal units one of the leading places belongs to terminology. For many decades, various problems of the theory of the term and special term systems have been intensively developed in Karakalpak linguistics. In this article, we will consider the study of the formation and learning of pedagogical Karakalpak terminology.